Non Linear Dynamics of an Electromagnetic / Levitation System - Cabal, Eisenover (2007)
This paper presents a mathematical model and the performance evaluation of a kind of electromagnetic levitation/suspension system, where the static and dynamic magnetic fields are linked through conductor bodies. The complex and nonlinear dynamic of the system, allows it to illustrate in a practical form, different aspects of automatic control like mathematical modelling, nonlinear analysis, simulating, controllers design, evaluation and validation of linear and nonlinear controllers. Also, the system allows to illustrate the basic principles of operation of the big developments in power applications, force generation and energy conversion. The performance evaluation is started from a model obtained by direct evaluation of mechanical forces of electromagnetic origin and virtual work method.